1995
DOI: 10.1080/00071669508417776
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus requirements of laying hens fed on wheat‐based diets

Abstract: 1. Three experiments were carried out to determine the phosphorus (P) requirements of laying hens aged 34 to 58 weeks (experiment 1), 59 to 70 weeks (experiment 2) and 22 to 50 weeks (experiment 3) given diets containing wheat, sorghum and soyabean meals as the main ingredients. Dietary total P (Pt) varied between 3.2 and 7.3 g/kg (experiment 1), 3.2 and 4.6 g/kg (experiment 2) and 3.0 and 6.6 g/kg (experiment 3). Hens were housed at either 18 degrees or 30 degrees C (experiments 1 and 2) and uncontrolled temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…This experiment confirms the findings of Newkirk et al (1993), Jeroch and Peter (1994), and Usayran and Balnave (1995) that exogenous phytase does not have the same positive effects in wheat-based diets as it does in corn-based diets. Positive effects of enzyme on production in the final period do not appear to be on the release of phytate P, and enzyme addition produced none of the negative effects of excess P. Usayran and Balnave (1995), Gordon and Roland (1998) and Um and Paik (1999) have suggested that the effect of phytase enzyme is not only on P release.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This experiment confirms the findings of Newkirk et al (1993), Jeroch and Peter (1994), and Usayran and Balnave (1995) that exogenous phytase does not have the same positive effects in wheat-based diets as it does in corn-based diets. Positive effects of enzyme on production in the final period do not appear to be on the release of phytate P, and enzyme addition produced none of the negative effects of excess P. Usayran and Balnave (1995), Gordon and Roland (1998) and Um and Paik (1999) have suggested that the effect of phytase enzyme is not only on P release.…”
Section: Discussionsupporting
confidence: 81%
“…Positive effects of enzyme on production in the final period do not appear to be on the release of phytate P, and enzyme addition produced none of the negative effects of excess P. Usayran and Balnave (1995), Gordon and Roland (1998) and Um and Paik (1999) have suggested that the effect of phytase enzyme is not only on P release. Newkirk et al (1993) described interactions between phytase and xylanase enzymes, suggesting that intestinal viscosity may influence the effect of phytase when wheat is fed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nys (1995), after Sauveur (1989, mentions that for a diet containing 300 units of plant origin phytase the amount of mineral phosphorus added to the diet can be reduced to 0.12%. Similar results were obtained by Usayran and Balnave (1995) who found that when a diet containing over 40% wheat and 200 U of plant origin phytase was used no insufficiency of phosphorus was observed even at 0.12% AP in the diet. In the experiments of these authors the addition of 500 U of microbial phytase to a diet containing 0.32 or 0.46% TP (0.12 or 0.24% AP, respectively) has a negative effect on laying rate and egg shell quality from hens consuming 125-128 g of feed with laying rate below 80%.…”
Section: Optimal Level Of Phytasesupporting
confidence: 77%
“…This assumption seems to confirm the results obtained by Keshavarz (1986) who found that, depending on P intake from the diet (540 -880 mg), the utilization of P ranged from 21.1 to 30.5%. According to Usayran and Balnave (1995), with daily intake of P between 352 and 837 mg, the utilization of this element ranged from 19 to 29% and was therefore similar to that observed by Keshavarz (1986).…”
Section: Phosphorus Balancementioning
confidence: 83%